2011
DOI: 10.1586/ehm.11.52
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for a randomized controlled trial comparing two prophylaxis regimens in adults with severe hemophilia A: the Hemophilia Adult Prophylaxis Trial

Abstract: A major goal of comprehensive hemophilia care is to prevent occurrence of bleeds by prophylaxis or regular preventive factor, one or more times weekly. Although prophylaxis is effective in reducing bleeding and joint damage in children, whether it is necessary to continue into adulthood is not known. The purpose of this article is to describe a Phase III randomized controlled trial to evaluate prophylaxis comparing two dose regimens in adults with severe hemophilia A. I hypothesize that adults with mature cart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Among so‐called ‘short‐acting’ FVIII products (ie, those that have not been modified to extend half‐life), effective prophylaxis at dosing regimens of <3 times/week has been demonstrated in few other prospective studies . Further studies with unmodified FVIII products are under way that will address effectiveness of less than 3‐times‐weekly dosing . Although recent studies have highlighted the high interpatient variability in FVIII pharmacokinetics following administration of comparable prophylactic doses , the pharmacokinetics of the administered drug may not be the only explanation for the effectiveness of a twice‐weekly dosing regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Among so‐called ‘short‐acting’ FVIII products (ie, those that have not been modified to extend half‐life), effective prophylaxis at dosing regimens of <3 times/week has been demonstrated in few other prospective studies . Further studies with unmodified FVIII products are under way that will address effectiveness of less than 3‐times‐weekly dosing . Although recent studies have highlighted the high interpatient variability in FVIII pharmacokinetics following administration of comparable prophylactic doses , the pharmacokinetics of the administered drug may not be the only explanation for the effectiveness of a twice‐weekly dosing regimen.…”
Section: Discussionmentioning
confidence: 99%
“…For further analyses, we did not use the dispersion of the PEI‐DB data in order to exclude CT heterogeneity of the PEI‐DB. A dispersion parameter of φ = 1.5 previously has been suggested as a conservative estimate, 20 which was, therefore, used. Notably, values up to φ = 7 have been used in some CT protocols for statistical analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Barriers to enrollment, including competing studies and lack of free study factor, were expected and typical of investigator-initiated rare disease trials [14]; other enrollment barriers were unexpected, including patient unwillingness to change prophylaxis frequency, constituting 37% of enrollment exclusions. These findings suggest that bleed severity and infusion difficulty do influence prophylaxis adherence in adults [13], and while the question of whether once-weekly prophylaxis is non-inferior to three-times weekly prophylaxis is unlikely to be answered, it does confirm the potential benefit of novel therapies that reduce treatment frequency.…”
Section: To the Editormentioning
confidence: 99%
“…This pilot study was not powered to test the non-inferiority of three-times weekly with once-weekly rFVIII prophylaxis in adults with severe haemophilia A; rather, it tested the feasibility of a future larger phase III randomized trial [12]. Prior to conducting this pilot study, preliminary sample size calculations indicated a sample size of 106 subjects, inflated to 124 for 15% attrition, would be required for a phase III randomized, cross-over, non-inferiority trial [13]. For this pilot study, a sample size of 20 subjects was considered sufficient for clinical reasons to determine the feasibility of approach and practicality of processes, e.g.…”
mentioning
confidence: 99%